(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This review paper explores the intricate interplay between forestry and human health, emphasizing a holistic perspective that integrates ecological, health, and social dimensions. As forests play a vital role in providing ecosystem services—such as biodiversity, carbon sequestration, and sources of food and medicine—they significantly impact public health outcomes. Despite these benefits, many communities face challenges related to health disparities, malnutrition, and mental health issues exacerbated by deforestation and habitat loss. This review highlights how forest ecosystems can mitigate climate change, enhance food security, and promote mental well-being through increased access to natural spaces. However, the ongoing threats posed by urbanization and environmental degradation limit these benefits, particularly for marginalized populations. It synthesizes existing research to identify the multifaceted ways in which forestry influences health and well-being, while also addressing the gaps in knowledge regarding the social and mental health impacts of forest loss. Ultimately, the paper advocates for integrated approaches to forestry management that prioritize public health, calling for interdisciplinary collaboration to develop sustainable practices that enhance both ecological integrity and human health. Through this comprehensive examination, the review aims to inform policymakers, stakeholders, and researchers about the critical connections between forestry and health, promoting a sustainable future for both ecosystems and communities.